Mycorrhization and grafting improve growth in the tomato and reduce the population of Nacobbus aberrans - Garita, Sebastián Andrés (2019)
Inoculation with mycorrhizal fungi and the use of rootstock that is tolerant or resistant to nematodes are two strategies that allow the nematode to be controlled, and plants to coexist with the pathogen. However, the two techniques have always been tested in isolation, when their positive effects are less compared to when they are able to act together. In the present work, two rootstocks combined with the mycorrhizal fungus Rhizophagus intraradices were compared, with the aim of evaluating their behaviour on the growth of tomato plants in soils infested with N. aberrans, the false root-knot nematode. The experiment was set up in a completely randomised design with ten replications, in a 3 x 2 x 2 factorial scheme. The treatments consisted of a combination of three factors: a) plant composition: two rootstocks (Solanum lycopersicum var. cerasiform ‘Carolina’ and S. lycopersicum ‘Maxifort’), onto which the ‘Santa Clara’ tomato (S. lycopersicum) was grafted, and a non-grafted plant, considered the control, which was the same cultivar as the graft; b) mycorrhization: mycorrhizal or non-mycorrhizal roots; c) a substrate infested or not infested with N. aberrans. The plants grafted onto ‘Maxifort’ showed significantly greater growth for shoot dry weight, root fresh weight and stem diameter. The rootstock under test had a lower pathogen reproductive factor than did the ungrafted plant. Mycorrhization contributed to a reduction in the number of days until flowering, and a reduction in the final population of N. aberrans for the three plant compositions under test.